2015
DOI: 10.7150/ijbs.12930
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR Pathway by Rapamycin Reduces Brain Damage in Rats Subjected to Transient Forebrain Ischemia

Abstract: The aims of this study are to clarify the role of mTOR in mediating cerebral ischemic brain damage and the effects of rapamycin on ischemic outcomes. Ten minutes of forebrain ischemia was induced in rats, and their brains were sampled after 3 h, 16 h, and 7 days reperfusion for histology, immunohistochemistry and biochemical analysis. Our data demonstrated that cerebral ischemia resulted in both apoptotic and necrotic neuronal death; cerebral ischemia and reperfusion led to significant increases of mRNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 65 publications
10
41
0
Order By: Relevance
“…However, inhibiting mTOR signaling pathway using rapamycin or knockdown of mTOR promotes autophagy and attenuates ischemia‐induced neuronal death 14, 15, 16, 26. Reports also demonstrate that inhibition of mTOR pathway suppresses autophagy, prevents cytochromecrelease and reduces ischemic brain damage 3, 15, 27. This discrepancy may result from different animal strains, ischemic model, the time and route of drug administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inhibiting mTOR signaling pathway using rapamycin or knockdown of mTOR promotes autophagy and attenuates ischemia‐induced neuronal death 14, 15, 16, 26. Reports also demonstrate that inhibition of mTOR pathway suppresses autophagy, prevents cytochromecrelease and reduces ischemic brain damage 3, 15, 27. This discrepancy may result from different animal strains, ischemic model, the time and route of drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although tremendous progress has been made in the study of pathophysiology on ischemic stroke, translation of basic research into clinical therapies has not successed. Currently, systemic thrombolysis with recombinant intravenous tissue plasminogen activator (rtPA) remains a frequently used therapy which can improve clinical outcome of patients with acute ischemic stroke 3, 4. However, rtPA has an increased risk of hemorrhage beyond a few hours of poststroke, and only less than 4% of stroke patients can benefit from it 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that improvement of mTOR activation may protect cerebral ischemic injury and enhance functional recovery [4]. Therefore, it has been generally accepted that mTOR has effective neuroprotective functions, although there is controversy regarding the effects of mTOR on ischemic injury [22526]. …”
Section: Discussionmentioning
confidence: 99%
“…Increases in autophagy following ischemia–reperfusion injury are well recognized. However, there are conflicting reports that increased autophagy following cerebral ischemia-reperfusion injury can be detrimental (Baek et al, 2014; Yang et al, 2015; Au et al, 2015; He et al, 2016; Xie et al, 2016) or neuroprotective (Carloni et al, 2012; Qi et al, 2014; Su et al, 2014; Wang et al, 2014; Jiang et al, 2015). Sex differences in autophagy both in vitro (Du et al, 2009) and in vivo following HI (Weis et al, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 99%